2007
DOI: 10.1016/j.jbiomech.2006.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Direct measurement of intervertebral disc maximum shear strain in six degrees of freedom: Motions that place disc tissue at risk of injury

Abstract: Human intervertebral disc specimens were tested to determine the regions of largest maximum shear strain experienced by disc tissues in each of three principal displacements and three rotations, and to identify the physiological rotations and displacements that may place the disc at greatest risk for large tissue strains and injury. Tearing of disc annulus may be initiated by large interlamellar shear strains. Nine human lumbar discs were tagged with radiographic markers on the endplates, disc periphery and wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
85
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(92 citation statements)
references
References 33 publications
6
85
1
Order By: Relevance
“…Thus, degenerated discs develop higher stresses while normal discs develop higher strains. Bending simulation shows that flexion, extension, right and left lateral loading causes convex and concave curvature in the disc, which implies combine tensile and compression stresses and higher strains which occurred in the disc posterior side, as reported elsewhere [24][25][26]. Torsion simulation showed large shearing in the annulus periphery, suggesting a main load carrier upon removal of posterior elements, as previously suggested by Refs.…”
Section: Fe Sim Loadssupporting
confidence: 81%
“…Thus, degenerated discs develop higher stresses while normal discs develop higher strains. Bending simulation shows that flexion, extension, right and left lateral loading causes convex and concave curvature in the disc, which implies combine tensile and compression stresses and higher strains which occurred in the disc posterior side, as reported elsewhere [24][25][26]. Torsion simulation showed large shearing in the annulus periphery, suggesting a main load carrier upon removal of posterior elements, as previously suggested by Refs.…”
Section: Fe Sim Loadssupporting
confidence: 81%
“…Gellan gum is bacterialderived and shows extremely high cytocompatibility in vitro and in vivo (Ahearne and Kelly, 2013;Anderson et al, 1988;Khang et al, 2015;Reitmaier et al, 2014). Recently, this material was reinforced to withstand higher compressive forces by addition of methacrylated modifications, resulting in a much stiffer hydrogel tuneable in the range of 0.15-148 kPa (Coutinho et al, 2010). This is similar to the crosslinking genipin approach that leads to shear stiffness in the range of 47-61.1 kPa, depending on the genipin concentration or up to 73 kPa, when fibrin is combined with genipin and fibronectin (Guterl et al, 2014).…”
Section: Reinforced Hydrogels For Intervertebral Disc Tissue Engineeringmentioning
confidence: 97%
“…For example, normal movement causes intradiscal pressures in the range of 0.1 MPa when reclining, 0.46 MPa for unsupported sitting, and 0.5 MPa for relaxed standing (Nachemson and Elfstrom, 1970;White and Panjabi., 1990;Wilke et al, 1999). Hence, a successful approach has to incorporate a biomaterial that can fulfil the requirements of withstanding a motion in six degrees of freedom (Costi et al, 2007;Guterl et al, 2013;Long et al, 2016b;Nerurkar et al, 2010), while providing nutrient delivery to the centre of the IVD and simultaneously allowing the transportation of metabolites out of the disc Kandel et al, 2008). Due to this challenging task, approaches that rely solely on biomaterials to restore disc height are more closely investigated.…”
Section: Current Challenges For Ivd Repairmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the interface between intervertebral discs and vertebral surfaces represents the most critical region for the onset of spinal diseases. Moreover, some recent studies (Costi et al, 2007;Wilson et al, 2003) showed how the shear effects are dominant in disc tissue failures. For these reasons, it was considered interesting to plot, for the more stressed disc, in Panjabi configuration (Panjabi et al 1994), the maps of the maximum shear stress for flexion and extension moments and to compare the distributions for the two models, with and without endplates, in order to underline how the presence of the endplates allow the reduction of the stress condition in the intervertebral disk.…”
Section: Stress Results Comparisonmentioning
confidence: 99%